Pengembangan WEPICSAL (Website Pembelajaran Interaktif Carrd.co Berbantuan Website Spasial) pada Materi Kubus dan Balok Kelas VI Sekolah Dasar - Rika Tri Kurnia Aprianti; Nurdiyah Kurniati; Mustamiroh; Sukriadi; Rizki Ramalia (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Mathematics is an essential subject taught at every level of education, and geometry, one of its branches most closely connected to students' daily lives, plays a key role in developing spatial ability, particularly through the cube and cuboid material taught in sixth grade. However, field observations revealed that teachers still commonly rely on conventional media such as cardboard cubes, resulting in students who struggle to visualize, construct, and represent three-dimensional shapes, indicating the need for an interactive learning medium to support this ability. This study aims to describe the development process of WEPICSAL (Website for Interactive Learning on Carrd.co Assisted by Spatial Website), an interactive web-based learning medium on cube and cuboid material for sixth-grade elementary school students, and to determine its validity and practicality. The medium was developed using the Research and Development method with the ADDIE model, comprising analysis, design, development, implementation, and evaluation. WEPICSAL uses Carrd.co as its display and navigation platform, supplemented by spatial websites, namely the Isometric Drawing Tool and 3D Builder Math Playground, and was designed with a Problem-Based Learning approach. The results show that WEPICSAL was successfully developed through all five ADDIE stages. Validity scores reached 77.5% from material experts and 94.7% from media experts, both indicating valid categories. Practicality reached 93.7% in the small-group trial, 96.9% in the large-group trial, and 96.3% based on teacher responses, all of which were categorized as highly practical. WEPICSAL is therefore considered a valid and practical learning medium for cube and cuboid material.